The Protection of Social Harmony: A Critical Study on the Prohibition of Cohabitation in Islamic Law and the Criminal Code (KUHP) - Sukiyawati Sukiyawati; Achmad Amin Majid; Sajida Himaniarah (SHAHIH: Journal of Islamicate Multidisciplinary, 2025)
This study analyzes the legal policy regulating the prohibition of living together without marriage from the perspective of Islamic law and the Criminal Code, as well as its implications for social order. This research uses a normative juridical method with a legislative, comparative legal, and conceptual approach. In addition, primary legal sources are the Quran, Hadith, and the Criminal Code, while secondary legal sources are books, journals, and news. The interpretation used is systematic and grammatical. The findings reveal that Islamic law prohibits cohabitation, considering it a form of zina (adultery/fornication) that undermines family values and societal morals. Meanwhile, the KUHP does not explicitly regulate cohabitation but uses provisions such as 'indecent acts' or 'cohabitating as spouses without marriage' (Article 284) to penalize offenders. While this prohibition aims to protect public order, it has also sparked criticism regarding privacy rights and individual freedoms. The study concludes that although the ban on cohabitation has moral and social justifications, a more balanced approach is needed to reconcile public interests with human rights.